Millennial Generation Leadership in the Work Environment for Gen Z Employees, Case Study: Improving Performance Ability and Employee Loyalty - Darmanto, Darmanto; Ali, Muhamad David; Ramzy, Hilmy Syaddad; Gifari, Muhammad Fauzan (Lentera Ilmu Nusantara, 2025)
The differences in character between Millennial leaders and Gen Z employees are a new challenge in the multigenerational workplace. This study aims to understand how Millennial leadership styles affect Gen Z performance and loyalty. Through a qualitative approach based on literature studies, it was found that transformational leadership that is open, supportive, and flexible can increase Gen Z work engagement and commitment. However, its success is highly dependent on the leader's ability to understand the emotional and professional needs of this generation. This study highlights the importance of adapting leadership styles in building effective working relationships across generations.